Titanium and steel fracture fixation plates with different surface topographies: Influence on infection rate in a rabbit fracture model. Issue 3 (March 2016) - Metsemakers, W.J.; Schmid, Tanja; Zeiter, Stephan; Ernst, Manuela; Keller, Iris; Cosmelli, Nicolo; Arens, Daniel; Moriarty, T. Fintan; Richards, R. Geoff
Abstract: Introduction: Implant-related infection is a challenging complication in musculoskeletal trauma surgery. In the present study, we examined the role of implant material and surface topography as influencing factors on the development of infection in an experimental model of plating osteosynthesis in the rabbit. Methods: The implants included in this experimental study were composed of: standard Electropolished Stainless Steel (EPSS), standard titanium (Ti-S), roughened stainless steel (RSS) and surface polished titanium (Ti-P). Construct stability and load-to-failure of Ti-P implants was compared to that of Ti-S implants in a rabbit cadaveric model. In an in vivo study, a rabbit humeral fracture model was used. Each rabbit received one of three Staphylococcus aureus inocula, aimed at determining the infection rate at a low, medium and high dose of bacteria. Outcome measures were quantification of bacteria on the implant and in the surrounding tissues, and determination of the infectious dose 50 (ID50 ). Results: No significant differences were observed between Ti-S and Ti-P regarding stiffness or failure load in the cadaver study. Of the 72 rabbits eventually included in the in vivo study, 50 developed an infection. The ID50 was found to be: EPSS 3.89 × 10 3 colony forming units (CFU); RSS 8.23 × 10 3 CFU; Ti-S 5.66 × 10 3 CFU; Ti-P 3.41 × 10 3 CFU. Significantly lower bacterial counts were found on the Ti-S implants samples compared with RSS implants ( p < 0.001) at the high inoculum. Similarly, lower bacterial counts were found in the bone samples of animals in the Ti-S group in comparison with both RSS and EPSS groups, again at the high inoculation dose ( p < 0.005). Conclusion: No significant differences were seen in susceptibility to infection when comparing titanium and steel implants with conventional or modified topographies. Ti-P implants, which have previously been shown in preclinical studies to reduce complications associated with tissue adherence, do not affect infection rate in this preclinical fracture model. Therefore, Ti-P implants are not expected to affect the infection rate, or influence implant stability in the clinical situation.